Faktor-Faktor Ibu Balita Yang Berhubungan Dengan Kepatuhan Follow Up Penderita Pnemonia Balita Di Puskesmas Cisaga, Ciamis, Jawa Barat - Mulyana, Agus; Prabamurti, Priyadi Nugraha; Adi, M. Sakundarno (Jurnal Promosi Kesehatan Indonesia, 2006)
Background: One of the important procedures in pneumonia treatment is to conduct a followup care. The follow-up care of pneumonia disease should be done at least two days after treatment or sometimes earlier when the patients have bad physical conditions. The cases of pneumonia children in Cisaga health centre have been increasing recently, and even have a higher percentage compare to the average national cases. However, the percentage of the follow-up care cases has only about 13.5% from the total cases. The objective of this study is to identify some factors associated with mother’s compliance to conduct a follow-up care oftheir children who suffered pneumonia at Cisaga health centre.Method : A cross sectional survey with 50 sample, which consists of 40 patients have done a follow-up care and 10 patients have never done a follow-up care, has been employed in this study. Chi-square test has been used to examine the associations between factors and mother’scompliance.Results : Chi-square test shows that there is an association between knowledge and mother’s compliance behaviour since p<0.05. However, mother’s education level, occupation, and family supports and income have no association with the mother’s compliance. The studysuggests that information, education and communication programs in terms of preventing and treating pneumonia disease in children under five including the causes, the treatment procedures, and the effects of the disease, have to be conducted intensively, particularly to mothers who have children suffering pneumonia.Keyword: Pneumonia, compliance behaviour, mother, follow-up care